Tripartite Motif Containing 65 Deficiency Confers Protection Against Acute Kidney Injury via Alleviating Voltage‐Dependent Anion Channel 1–Mediated Mitochondrial Dysfunction - Tao Chen; Yang Zhang; Liting Ding; Chenlu Xiong; Chao Mei; Sisi Wei; Ming Jiang; Yingjie Huang; Jianrong Chen; Tao Xie; Qing Zhu; Qi Zhang; et al. (MedComm)
ABSTRACT Acute kidney injury (AKI) is a prevalent and serious clinical disease with a high incidence rate and significant health burden. The limited understanding of the complex pathological mechanisms has hindered the development of efficacious therapeutics. Tripartite motif containing 65 (TRIM65) has recently been identified as a key regulator of acute inflammation. However, its role in AKI remains unclear. The present study observed that TRIM65 expression was upregulated in AKI. Moreover, the knockout of the Trim65 gene in mice exhibited a substantial protective impact against rhabdomyolysis, ischemia‐reperfusion (I/R), and cisplatin‐induced AKI. Mechanistically, TRIM65 directly binds and mediates K48/K63‐linked polyubiquitination modifications of voltage‐dependent anion channel 1 (VDAC1) at its K161 and K200 amino acid sites. TRIM65 plays a role in maintaining the stability of VDAC1 and preventing its degradation by the autophagy pathway. TRIM65 deficiency attenuates mitochondrial dysfunction in renal tubular epithelial cells during AKI. Conversely, the overexpression of VDAC1 in renal tissues has been demonstrated to negate the protective effect of TRIM65 deficiency on AKI. These findings suggest that TRIM65 may play a role regulating of AKI through the targeting of VDAC1‐dependent mitochondrial function, offering potential avenues for the development of new drug targets and strategies for the treatment of AKI.